2007
DOI: 10.1681/asn.2007010022
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk after Parathyroidectomy among Chronic Hemodialysis Patients

Abstract: The impact of parathyroidectomy (PTX) on the long-term risks for hip and other fractures is unknown. Uncontrolled case series have reported an increase in bone mineral density after PTX. However, very low serum parathyroid hormone levels have been associated with decreased bone mineral density, adynamic bone disease, and fractures. This study compared long-term fracture rates among hemodialysis patients who underwent PTX with a matched control group. Data were obtained from the US Renal Data System. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 35 publications
5
85
0
4
Order By: Relevance
“…The reduction in clinical fractures observed with cinacalcet treatment in this study was similar to that observed in a case control study of surgical parathyroidectomy in the United States that demonstrated a 32% reduction in subsequent hip fractures. 31 The importance of PTH as a biomarker of abnormal bone is controversial. 32,33 Cohort studies have shown an increased risk of fracture associated with low PTH 12,29,30 or very high PTH.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in clinical fractures observed with cinacalcet treatment in this study was similar to that observed in a case control study of surgical parathyroidectomy in the United States that demonstrated a 32% reduction in subsequent hip fractures. 31 The importance of PTH as a biomarker of abnormal bone is controversial. 32,33 Cohort studies have shown an increased risk of fracture associated with low PTH 12,29,30 or very high PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, left ventricular function in patients with advanced sHPT and dilated cardiomyopathy was markedly improved by PTx. 40 Other possible mechanisms for post-PTx survival improvement include reduction in fracture risk; 41 improvement in anemia and hypertension, 42 cardiac autonomic nervous system, 43 life-threatening condition of calciphylaxis, 44 immune system, 45 muscle strength, 46 as well as sustained reduction in fibroblast growth factor 23.…”
Section: Discussionmentioning
confidence: 99%
“…KMD'deki iyileşme genellikle postoperatif 1.aydan itibaren başlamaktadır. Rudsder ve ark.nın çalışmasında paratiroidektomi yapılan hastalarda herhangi bir kırık ve kalça kalça kemiği kırığı riskinde anlamlı azalma gözlenmiştir (23). Mortalite riski açısından da önemli çalışmalar bulunmaktadır.…”
Section: Operasyon Ve Tipleriunclassified